2007
DOI: 10.1189/jlb.0507335
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein up-regulates anergy-related genes and a new set of genes, which affects T cell homeostasis

Abstract: Hepatitis C virus (HCV) infection is the main cause for chronic hepatitis, leading to cirrhosis and hepatic carcinoma. Virally induced immune dysfunction has been called as the cause for viral persistence. Previous results demonstrate that CD4 Jurkat cells stably expressing the HCV core protein show an increased activation of NFAT transcription factor and an impaired IL-2 promoter activity, affecting intracellular signaling pathways in a manner that mimics clonal anergy. We had shown previously that NFAT activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 85 publications
7
37
1
Order By: Relevance
“…The gene expression changes seen in AML T cells are not purely due to the normal signaling seen on T-cell activation 26 and not supportive of an anergic state. 27 Our results are in keeping with the hypothesis that both CD4 and CD8 T cells in AML have undergone an aberrant activation process. Comparison of the gene lists with those generated from our previous studies in CLL 4 demonstrated little commonality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The gene expression changes seen in AML T cells are not purely due to the normal signaling seen on T-cell activation 26 and not supportive of an anergic state. 27 Our results are in keeping with the hypothesis that both CD4 and CD8 T cells in AML have undergone an aberrant activation process. Comparison of the gene lists with those generated from our previous studies in CLL 4 demonstrated little commonality.…”
Section: Discussionsupporting
confidence: 91%
“…These data are in keeping with the fact that the gene expression changes seen in T cells from patients with AML are not simply due to the normal signaling that occurs on T-cell activation. A search for 14 anergy-related genes 27 within the AML versus healthy gene lists further revealed the differential expression of only 2 genes, namely JMJD2B and RAB10. These microarray results were validated using qRT-PCR for 5 differentially expressed genes (ACTN1, ATM, CD48, FOSB, and JUN).…”
Section: Abnormal Gene Expression Profile Of T Cells In Amlmentioning
confidence: 99%
“…Likewise, HCV core protein is able to downregulate CD4 ϩ lymphocyte responses by inducing anergy through activation of NFAT with no concurrent activation of AP-1 or NF-B [50]. HCV, however, did not alter the allogeneic-induced up-regulation of CD28 or KIR2D molecules in liver recipients from our series, suggesting that molecule downregulation induced by CMV follows specific pathways.…”
Section: Discussioncontrasting
confidence: 68%
“…However, the results of our two kinds of experiments (plasmids and lenti-virus) consistently showed that the expression of HCV-core protein in T lymphocytes could enhance the Th17 development. Other groups previously reported that HCV-core protein could affect anergy-related genes and T cell responses by inducing spontaneous and alternating T-cell receptor-triggered Ca2+ oscillations[37], [38]. Therefore, the expression of HCV-core protein in T lymphocyte might be important for the functional changes in T lymphocytes.…”
Section: Discussionmentioning
confidence: 97%